Use of methylphenidate by university students in the health area (Research, Society and Development, 2021)
Methylphenidate is the drug most frequently used in the treatment of attention deficit hyperactivity disorder. However, due to its psychostimulant properties, this substance has been used to stimulate productivity and increase intellectual capacity in several areas of study. In this work, the characteristics of the use of methylphenidate among pharmacy, nursing, and medical students of a university in the capital of Bahia were analyzed. In this cross-sectional study, 338 students from different semesters of the aforementioned courses were interviewed. The instrument used for data collection was a standardized self-completed questionnaire applied by the researchers. Altogether, 76% of respondents were female and the average age was 22 years old. The frequency of students who used or who had already used methylphenidate at some point in their academic life was higher among medical students (12%). The main justification for the use of this substance was the higher concentration to study (59%). Also, 92% of respondents claimed to use Methylphenidate without medical supervision and 80% indicated the time of the tests as the time of greatest use of this drug. These results show high non-prescribed use of methylphenidate among health care students.